2005
DOI: 10.1016/j.compositesa.2004.11.004
|View full text |Cite
|
Sign up to set email alerts
|

The influence of fibre length and concentration on the properties of glass fibre reinforced polypropylene. 6. The properties of injection moulded long fibre PP at high fibre content

Abstract: The results of an investigation of the mechanical performance of injection moulded long glass fibre reinforced polypropylene with a glass fibre content in the range 0-73 weight % are presented. The composite modulus exhibited a linear dependence on fibre content over the full range of the study. Composite strength and impact resistance exhibited a maximum in performance in the 40-50 weight % reinforcement content range. The residual fibre length and fibre orientation in the samples has also been characterised.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
125
1
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(133 citation statements)
references
References 33 publications
5
125
1
2
Order By: Relevance
“…The impact strength increases almost linearly with the fibre weight content and reaches an asymptote (plateau) when fibres are longer than 6 mm. More recently, the same author reported that the notched impact strength is the highest when fibre contents are in the range 40-50 wt%, whereas the maximum of the unnotched impact strength appears at a fibre content of about 30 wt% only [8]. The impact strength quickly drops above these limits.…”
mentioning
confidence: 91%
See 1 more Smart Citation
“…The impact strength increases almost linearly with the fibre weight content and reaches an asymptote (plateau) when fibres are longer than 6 mm. More recently, the same author reported that the notched impact strength is the highest when fibre contents are in the range 40-50 wt%, whereas the maximum of the unnotched impact strength appears at a fibre content of about 30 wt% only [8]. The impact strength quickly drops above these limits.…”
mentioning
confidence: 91%
“…The impact strength quickly drops above these limits. Moreover, as for the tensile or flexural strengths [5,8,10,14,15] different authors evidenced that the residual fibre length and the fibre orientations influence the impact strength [8,21]. In the case of PP reinforced with 50 wt% glass fibres having initial fibre length of 10 mm (reduced to 1.8-2.0 mm after injection moulding), Skourlis et al [22] furthermore highlighted the influence of the thickness of the skin and core layers of the part, induced by the shear and fountain flows during processing.…”
mentioning
confidence: 99%
“…During the compounding process, filamentization of fiber bundles and fracture of the resultant monofilaments into elements of a lower aspect ratio lead to the dispersion of fibers into the polymer matrix [12]. For high content fiber composites, the presence of fiber bundles seems to be unavoidable which could result in a reinforcement with a much lower aspect ratio and effective stiffness than well-dispersed fibers, consequently giving a lower and even decreasing stiffness [13]. However, the existing stiffness models assume the fibers are fully and evenly dispersed in the matrix.…”
Section: Introductionmentioning
confidence: 99%
“…The Thomason's works on the LGF reinforced polypropylene can support this hypothesis in this way on reflection, at least in the range of 10 to 40 wt% fibre content. 24 On this base, an empirical model of six parameters (15 conditions Table 1) can be elaborated (equation 3). In that case the material structure (residual fibre length, fibre orientation, crystallinity degree .…”
Section: Development Of the Analytical Modelmentioning
confidence: 99%